Poly (L-D) lactic acid grafted copolymer as well as preparation method and application thereof

By performing maleic anhydride graft copolymerization reaction on polylactic acid materials, the problem of insufficient heat resistance and toughness of polylactic acid materials is solved, and its grafting rate and performance are improved, and the preparation of high molecular weight polylactic acid copolymers is realized. Suitable for industrial production and various application fields.

CN119264389AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310813171.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

The existing polylactic acid materials have problems such as poor heat resistance, low toughness and insignificant modification of polyL-lactic acid, and are difficult to perform graft modification on the structural regularity and side chains of polyL-lactic acid, which affects its industrial application.

Method used

Using a preparation method of polyL-D lactic acid graft copolymer, maleic anhydride grafted L-lactide and D-lactide are obtained by polymerizing maleic anhydride with L-lactide and D-lactide respectively. Latide is then prepolymerized at low temperature and finally polymerized at high temperature to obtain a high molecular weight maleic anhydride grafted polyL-D lactic acid copolymer, which improves its toughness and heat resistance.

Benefits of technology

The maleic anhydride grafting rate has been improved, the toughness and elongation of break of polylactic acid materials have been improved, the glass transition temperature has been increased, the green degradability of the material and the ease of industrial production have been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264389A_ABST
    Figure CN119264389A_ABST
Patent Text Reader

Abstract

The invention provides a poly-L-D lactic acid grafted copolymer, which is a compound with a structure shown in the following general formula, R1, R2,... and Rn are respectively and independently selected from H or # imgabs 0 #, and in R1, R2,... and Rn, the molar percentage of R1, R2,... and Rn is not less than 15% of the molar percentage of # imgabs 1 #. L-lactide and D-lactide are respectively subjected to a grafting reaction with maleic anhydride, obtained products are mixed, low-temperature oligomerization is performed, high-temperature polymerization is performed, and the maleic anhydride grafted poly-L-D lactic acid copolymer material is obtained. A brand new synthetic route is provided, the grafting reaction of maleic anhydride is carried out before lactide polymerization, the grafting efficiency is greatly improved, the molecular weight of the polymer is increased, more maleic anhydride polar groups are successfully introduced to the side chain of poly-L-D lactic acid through the grafting reaction, and the toughness and elongation at break of the poly-L-D lactic acid material are improved. # imgabs2 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a technology for synthesizing polylactic acid by ring-opening polymerization of lactide, and in particular to a method for preparing a high molecular weight poly LD lactic acid graft copolymer, and belongs to the field of polymer material synthesis. Background Art

[0002] With the continuous development of the economy and society, people's production and life are increasingly dependent on fossil energy. However, non-renewable energy such as oil and coal is in short supply, and the consumption of these energy sources also seriously pollutes the environment. Petroleum-based materials are non-degradable, so it is necessary to find green resources that can replace petroleum to alleviate the pressure of resource shortage. Therefore, in recent years, the research on bio-based composite materials has become a hot topic in academia and industrial production, aiming to reduce the harm of fossil energy consumption to the natural environment. Compared with polyolefins and polyethylene terephthalate commonly used in industrialized commodities, polylactic acid (PLA) has better strength and processing properties. It is a thermoplastic resin generated by polymerization of lactic acid monomers, and lactic acid can be made by fermentation of plants such as corn, potatoes, cotton, and hemp. The raw materials can be recycled and have the advantages of high strength, good processing, and excellent mechanical properties. However, PLA also has some defects, such as high brittleness, strong hydrophobicity, low impact strength, and high price. At the same time, PLA has poor stability at high temperature and certain humidity. These shortcomings limit its application range.

[0003] At present, there are two main technologies for preparing polylactic acid at home and abroad (one-step method and two-step method). The one-step method is to use protonic acid or metal oxide catalysts to directly polymerize lactic acid to generate polylactic acid under vacuum and heating conditions. This method has a low molecular weight of polylactic acid and is not suitable for industrial application. The two-step method is often used to prepare polylactic acid in industry. In the first step, lactic acid is allowed to generate lactide under the action of a catalyst. In the second step, polylactic acid is generated by ring-opening polymerization under reduced pressure and the action of a catalyst. Then, a polylactic acid material with high optical purity is obtained through purification technology. There are many key factors that affect the preparation of polylactic acid. First, the optical purity of the lactide raw material for synthesizing polylactic acid must be no less than 99%. In addition, the residual free acid and water molecules in the lactide preparation process will also affect the polymerization of polylactic acid; secondly, the polymerization mechanism of polylactic acid synthesized from lactide can be divided into cationic ring-opening polymerization, anionic ring-opening polymerization and coordination polymerization. The polymerization methods will also be different when different catalysts are used. The ring-opening polymerization of lactide to synthesize polylactic acid is prone to racemization and oxidation reactions under high temperature reaction conditions, which have a certain impact on the purity of the product; finally, the residual lactide monomers in the polylactic acid product that have not participated in the ring-opening polymerization need to be removed in time, otherwise it will affect the purity and molecular weight of the polylactic acid product.

[0004] Polylactic acid has the disadvantages of being brittle, hydrophobic, and having low toughness. Therefore, it is difficult to directly prepare industrial products with polylactic acid materials like general-purpose plastics such as polyethylene and polypropylene, and it must be modified and processed. Currently, the most commonly used method is to optimize its performance by blending polylactic acid with other plastics. Although this method is simple, it does not fundamentally change the properties of polylactic acid materials. In addition, some studies have modified the polylactic acid material itself, such as grafting modification, and maleic anhydride is a good grafting modifier. Maleic anhydride is a polar monomer material with a five-membered ring structure. By grafting polylactic acid with maleic anhydride, on the one hand, the polarity of the polylactic acid material can be improved, and on the other hand, due to the ring structure, the toughness of the polylactic acid macromolecular chain can be modified at the same time. At present, the more commonly used methods at home and abroad are to graft maleic anhydride onto polyethylene, polystyrene, starch, lignin, etc., and then add them to the polylactic acid material by blending, so as to improve the toughness of polylactic acid, but the modification effect of this method is not obvious; some studies directly graft maleic anhydride onto the polylactic acid macromolecular chain by reactive extrusion, thereby changing the non-polar structure of polylactic acid. Although this method is simple, the grafting rate is low and the modification effect is not significant.

[0005] In patent FR2916203A1, a certain amount of polylactic acid particles and maleic anhydride monomers are mixed and added to a screw extruder. Under the protection of an initiator and an inert gas, high-temperature reactive extrusion is performed to prepare maleic anhydride grafted polylactic acid. Although maleic anhydride grafted polylactic acid material is successfully prepared by screw extrusion reaction, the grafting rate is less than 1%, and the modification effect on the polylactic acid material is general. In patent CN105315412A, a certain amount of DL-lactide and glycolide are polymerized at high temperature under the action of a catalyst to prepare poly(lactide-glycolide), which is then mixed with maleic anhydride after purification, and melt-grafted in a reactor under the action of an initiator to prepare maleic anhydride grafted poly(lactide-glycolide). This technology first prepares poly(lactide-glycolide), and then performs a melt maleic anhydride grafting reaction on poly(lactide-glycolide). Although maleic anhydride grafted poly(lactide-glycolide) is successfully prepared on poly(lactide-glycolide), the maleic anhydride grafting rate is less than 2%. In Chinese patent CN103570884A, crude poly(lactide-glycolide) (MPLGA) is prepared by using L / D-lactide, glycolide and maleic anhydride stannous octoate as a catalyst, and refined MPLGA is obtained after purification; the advantage is that the prepared polymer has a narrow molecular weight distribution, but maleic anhydride grafting reaction is carried out simultaneously during the polymerization process, the grafting rate is low, the polymerization time is long, and the polymer molecular weight is low, which is not conducive to industrial production.

[0006] In summary, the current processes for the preparation and modification of polylactic acid have the following main problems: (1) Pure polylactic acid products have poor heat resistance and low toughness, and require modification processing for industrial application. (2) Simply adding plasticizers and toughening agents to polylactic acid materials cannot fundamentally improve the thermodynamic properties of polylactic acid. (3) The grafting or esterification reaction on the side chain or end group of the polylactic acid macromolecular chain has low reaction activity and poor modification effect. (4) Due to the regular structure of poly (L-lactic acid) and the steric hindrance of the side chain structure, it is difficult to graft and modify poly (L-lactic acid) alone. Summary of the invention

[0007] In view of the above shortcomings, the present invention provides a poly LD lactic acid graft copolymer and a preparation method thereof, which adopts a reaction route different from the prior art to prepare a maleic anhydride grafted poly LD lactic acid copolymer material (MA-PLDLA) with a higher molecular weight. The maleic anhydride grafting rate is high, and the MA-PLDLA material has good toughness and heat resistance, is green and degradable, and is easy to industrialize.

[0008] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0009] The technical purpose of the first aspect of the present invention is to provide a poly LD lactic acid graft copolymer, which is a compound having a general formula I structure:

[0010]

[0011] Where R1, R2, ... and R n are independently selected from H or And R1, R2, ... and R n In the equation, R1, R2, ... and R n for The molar percentage is not less than 15%, preferably 15%-85%, more preferably 20%-80%, further preferably 30%-70%, most preferably 40%-60%.

[0012] Furthermore, the weight average molecular weight of the poly LD lactic acid graft copolymer is 1.5×10 5 -4.5×10 5 , preferably 2.0×10 5 -4.0×10 5 .

[0013] Furthermore, the right-angle tear strength of the poly LD lactic acid graft copolymer is not less than 130 kN / m, preferably 140-160 kN / m; the elongation at break is not less than 35%, preferably 40-60%, and the glass transition temperature is 90-110°C.

[0014] In the present invention, the right-angle tear strength and elongation at break are measured by a universal mechanical tester; the weight average molecular weight is measured by a gel chromatography method; and the glass transition temperature is measured by a differential scanning calorimeter method; which are described in detail below.

[0015] The technical purpose of the second aspect of the present invention is to provide a method for preparing a poly LD lactic acid graft copolymer, comprising the following contents:

[0016] (1) mixing L-lactide, maleic anhydride and an initiator to react to obtain maleic anhydride grafted L-lactide (MA-LLA), and purifying the product; mixing D-lactide, maleic anhydride and an initiator to react to obtain maleic anhydride grafted D-lactide (MA-DLA), and purifying the product;

[0017] (2) mixing the MA-LLA, MA-DLA, catalyst and initiator obtained in (1), and prepolymerizing at low temperature to obtain MA-LDLA oligomer;

[0018] (3) The MA-LDLA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain a maleic anhydride grafted poly-LD lactic acid copolymer material (MA-PLDLA).

[0019] Furthermore, the initiator in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, preferably dicumyl peroxide; and the amount of the initiator added is 0.1-5% by weight of L-lactide or D-lactide, preferably 0.5-2.0%.

[0020] Furthermore, step (1) is carried out at a constant temperature under an inert gas flow, preferably a nitrogen flow, and vacuum conditions, the reaction temperature is 50-150°C, preferably 80-120°C, the reaction pressure is 2-100 kPa, preferably 20-60 kPa; the reaction time is 0.5-10 h, preferably 2-6 h; the gas flow rate of the nitrogen flow protection is 0.5-6 m / s, preferably 2-4 m / s; and the amount of maleic anhydride added is 100-300% of the weight of L-lactide or D-lactide, preferably 150-200%.

[0021] Furthermore, the optical purity of the L-lactide and D-lactide in step (1) is 99.0-99.6%, preferably 99.4-99.6%, and homemade or purchased L-lactide and D-lactide can be used.

[0022] The main reaction occurring in step (1) is shown below:

[0023]

[0024] Furthermore, the purification in step (1) is to remove L-lactide and D-lactide that are not involved in the grafting reaction by vacuum distillation to obtain purified maleic anhydride grafted L-lactide (MA-LLA) and maleic anhydride grafted D-lactide (MA-DLA). Specifically, the vacuum distillation temperature is 100-200°C, preferably 120-150°C; the pressure is 0-100kPa, preferably 10-50kPa; and the time is 1-10h, preferably 2-6h.

[0025] Furthermore, in step (2), the catalyst is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride, preferably stannous octoate; and the initiator is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine, preferably triphenylphosphine.

[0026] Furthermore, in step (2), based on the weight of MA-LLA, the amount of MA-DLA added is 20-120%, preferably 40-100%, the amount of catalyst added is 0.2-10%, preferably 1-6%, and the amount of initiator added is 0.1-10%, preferably 1-5%, of MA-LLA.

[0027] Furthermore, step (2) is a low-temperature polymerization under an inert gas flow, preferably a nitrogen flow, and negative pressure conditions, the polymerization reaction temperature is 100-150°C, preferably 120-140°C; the reaction time is 2-15h, preferably 3-8h; the reaction pressure is 100-1000kPa, preferably 200-500kPa; the gas flow rate of the nitrogen flow is 0.5-6m / s, preferably 2-4m / s.

[0028] Furthermore, the antioxidant in step (3) is one of phosphites, alkyl polyphenols and thiobisphenols, preferably triphenyl phosphite, and the amount of the antioxidant added is 1%-10% by weight of the MA-LLA oligomer, preferably 2-6%.

[0029] Furthermore, the polymerization reaction temperature in step (3) is 150-250°C, preferably 160-200°C.

[0030] Furthermore, step (3) uses a twin-screw extruder to realize the reaction process, and MA-LLA oligomer, MA-DLA oligomer and antioxidant are added to the twin-screw extruder for polymerization reaction, and high-temperature reactive mixing and extrusion granulation are performed to finally obtain maleic anhydride grafted poly LD lactic acid copolymer material (MA-PLDLA).

[0031] The main reaction process of steps (2) and (3) is shown below:

[0032]

[0033] The technical purpose of the third aspect of the present invention is to provide the application of the above-mentioned poly LD lactic acid graft copolymer, and the poly LD lactic acid graft copolymer is used in the fields of agricultural mulch film, food packaging and medical hygiene products.

[0034] Compared with the existing technology, the present invention has the following advantages:

[0035] (1) Compared with the prior art, the present invention provides a new route for synthesizing poly (LD) lactic acid graft copolymers. First, maleic anhydride (MA) is polymerized with L-lactide (LLA) and D-lactide (DLA) respectively to obtain copolymers of maleic anhydride and lactide MA-LLA and MA-DLA. Then, MA-LLA and MA-DLA are prepolymerized at low temperature to obtain MA-LDLA oligomers. Finally, high-temperature polymerization is performed to obtain high molecular weight maleic anhydride grafted poly (LD) lactic acid copolymers.

[0036] (2) The method of the present invention first performs a grafting reaction of maleic anhydride before the polymerization of lactide, which greatly improves the grafting efficiency and increases the molecular weight of the polymer. More maleic anhydride polar groups are successfully introduced into the side chains of poly LD lactic acid through the grafting reaction, thereby improving the toughness and elongation at break of the poly LD lactic acid material.

[0037] (3) The present invention solves the problem of difficulty in introducing maleic anhydride groups into the side chains of poly (L-lactic acid) and low grafting rate due to the regular structure of poly (L-lactic acid) and steric hindrance in the side chain structure by adding a portion of maleic anhydride grafted D-lactide and copolymerizing with maleic anhydride grafted L-lactide.

[0038] (4) The product of the present invention retains the terminal hydroxyl group of the graft copolymer, so that the graft copolymer can be further modified through the functional group to further control the properties of the copolymer.

[0039] (5) Due to the introduction of a large amount of maleic anhydride ring structure on the side chain of poly LD lactic acid, the glass transition temperature of the poly LD lactic acid material is increased, and the prepared grafted modified poly LD lactic acid copolymer material is green and fully biodegradable.

[0040] (6) The bulk prepolymerization of L-lactide is carried out in a reactor and coupled with a twin-screw extruder for copolymerization. The reaction operation is simple and easy to industrialize.

[0041] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0042] The following non-limiting examples can enable those of ordinary skill in the art to more fully understand the present invention, but do not limit the present invention in any way. The reagents, materials, and instruments involved in the following examples, unless otherwise specified, can all be obtained through regular commercial channels. The tests and inspection methods involved in the following examples, unless otherwise specified, are all existing tests and inspection methods in the prior art. The following examples provide a clear and complete description of the technical scheme of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. All obvious changes or changes derived from the present invention still fall within the scope of protection of the present invention.

[0043] The following are the test methods for the performance parameters involved in the embodiments:

[0044] (1) Grafting rate of grafted groups:

[0045] The grafting rate of the grafted groups in the polylactic acid graft copolymer was determined by a chemical titration method, specifically: a certain mass of the polylactic acid graft copolymer was weighed and placed in a conical flask, a certain amount of tetrahydrofuran was added to dissolve it, and a small amount of thymol blue / DMF indicator was added dropwise; it was titrated with an excess of 0.05 mol / L potassium hydroxide ethanol solution, and back-titrated with 0.01 mol / L HCl-isopropanol solution.

[0046] Grafting rate = n2 / n1×100%, n1 = (m0-m2) / M1, n2 = m2 / M2, that is, grafting rate = [(0.05V KOH -0.01V HCl )×2×M1] / [m0-(0.05V KOH -0.01V HCl )×2×M2]; where m0 is the mass of the weighed polylactic acid graft copolymer, in g; m2 is the total mass of the grafted groups on the polylactic acid molecular chain, calculated based on the consumed KOH; n1 is the degree of polymerization of polylactic acid, i.e., the amount of substance of the lactic acid unit, n2 is the amount of substance of the grafted groups on the polylactic acid molecular chain, M1 is the molar mass of lactic acid, M2 is the molar mass of the grafted groups, V KOH V is the volume of potassium hydroxide ethanol solution added, in mL; HCl The volume of HCl-isopropanol solution consumed in titration, in mL.

[0047] (2) Right-angle tear strength and elongation at break: measured using a universal mechanical testing machine in accordance with GB / T1039-1992.

[0048] (3) Glass transition temperature: measured by differential scanning calorimeter (DSC) (DSC 204, NETZSCH, Germany). Test conditions: sample weight 5-10 mg, firstly, the sample was heated from room temperature to 200°C at a heating rate of 10°C / min, and kept isothermally for 5 min to eliminate the thermal history of the sample; then, the sample was quickly cooled to -20°C, and then heated from -20°C to 200°C at a heating rate of 10°C / min; nitrogen was introduced as protective gas during the entire test, and the flow rate of nitrogen was set to 50 mL / min.

[0049] (4) Polymer weight average molecular weight: measured by gel permeation chromatography (GPC) using gel permeation chromatography (GPC Waters 1515 system) to characterize the molecular weight of the polylactic acid graft copolymer sample. Chromatographically pure THF was used as the mobile phase, the flow rate was 1.0 ml / min, and the column temperature was 35°C. Before the test, the sample was dissolved in THF at a concentration of 5 mg / mL, filtered through a polytetrafluoroethylene (PTFE) filter membrane with a pore size of 0.22 μm, and then injected, and calibrated with a narrow distribution polystyrene (PS) standard.

[0050] (5) Detection of terminal hydroxyl groups: measured using the phthalic anhydride method in accordance with GB / T 12008.3-2009.

[0051] Example 1

[0052] (1) Add L-lactide and maleic anhydride to a reaction kettle, add dicumyl peroxide as an initiator, and react at a constant temperature under nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted L-lactide polymer; add D-lactide and maleic anhydride to another reaction kettle, add dicumyl peroxide as an initiator, and react at a constant temperature under nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted D-lactide polymer. The reaction temperature of the above two grafting modifications is 95°C, the reaction pressure is 35kpa, the reaction time is 2h, and the gas flow rate of the nitrogen flow protection is 2m / s; based on the weight of L-lactide or D-lactide, the amount of maleic anhydride added is 150% of L-lactide or D-lactide, and the amount of dicumyl peroxide is 0.5% of L-lactide or D-lactide.

[0053] (2) removing the L-lactide and D-lactide that did not participate in the grafting reaction in step (1) by vacuum distillation to obtain purified maleic anhydride grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature is 125° C., the pressure is 15 kPa, and the time is 2 h.

[0054] (3) MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, respectively, while adding a nitrogen flow and negative pressure to obtain MA-LLA oligomers and MA-DLA oligomers; the reaction temperature of the low temperature prepolymerization is 130° C., the reaction time is 3 h, the reaction pressure is 300 kPa, the gas flow rate of the nitrogen flow protection is 3 m / s, and the catalyst stannous octoate is 1% of the weight of MA-LLA or MA-DLA; the initiator triphenylphosphine is 1% of the weight of MA-LLA or MA-DLA.

[0055] (4) The MA-LLA oligomer and the MA-DLA oligomer of step (3) are simultaneously added into a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and high-temperature reactive mixing and extrusion granulation are performed to finally obtain a maleic anhydride grafted poly-LD lactic acid copolymer material (MA-PLDLA); based on the weight of the MA-LLA oligomer, MA-DLA is 30% of the MA-LLA, and the antioxidant triphenyl phosphite is 2% of the MA-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 180°C.

[0056] Performance characterization: The right-angle tear strength of the maleic anhydride grafted poly LD lactic acid copolymer material was measured to be 140 KN / m, the elongation at break was 38%, the glass transition temperature was 93°C, and the molecular weight of the polymer was 2.80×10 5 The maleic anhydride grafting rate of the polymer was determined to be 46.1% by chemical titration method, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.

[0057] Example 2

[0058] (1) L-lactide and maleic anhydride are added to a reaction kettle, and dicumyl peroxide as an initiator is added, and the reaction is carried out at a constant temperature under nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted L-lactide polymer; D-lactide and maleic anhydride are added to another reaction kettle, and dicumyl peroxide as an initiator is added, and the reaction is carried out at a constant temperature under nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted D-lactide polymer. The reaction temperature of the above two grafting modifications is 100°C, the reaction pressure is 35kpa, the reaction time is 3h, and the gas flow rate of the nitrogen flow protection is 2.5m / s; based on the weight of L-lactide / D-lactide, maleic anhydride is 160% of L-lactide / D-lactide, and dicumyl peroxide is 1.0% of L-lactide / D-lactide.

[0059] (2) removing the L-lactide and D-lactide that did not participate in the grafting reaction in step (1) by vacuum distillation to obtain purified maleic anhydride grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature is 130° C.; the pressure is 15 kPa, and the time is 2.5 h.

[0060] (3) MA-LLA and MA-DLA obtained in step (2) are respectively subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, and nitrogen flow and negative pressure conditions to obtain MA-LLA oligomers and MA-DLA oligomers; the reaction temperature of the low-temperature prepolymerization is 135° C., the reaction time is 4 hours, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3 m / s, and the catalyst stannous octoate is 2% of the weight of MA-LLA or MA-DLA; the initiator triphenylphosphine is 2% of the weight of MA-LLA or MA-DLA.

[0061] (4) The MA-LLA oligomer and the MA-DLA oligomer of step (3) are simultaneously added into a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and high-temperature reactive mixing and extrusion granulation are performed to finally obtain a maleic anhydride grafted poly-LD lactic acid copolymer material (MA-PLDLA); based on the weight of the MA-LLA oligomer, MA-DLA is 40% of the MA-LLA, and the antioxidant triphenyl phosphite is 3% of the MA-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 180°C.

[0062] Performance characterization: The right-angle tear strength of the maleic anhydride grafted poly LD lactic acid copolymer material was measured to be 145KN / m, the elongation at break was 41%, the glass transition temperature was 96°C, and the molecular weight of the polymer was 3.03×10 5 The maleic anhydride grafting rate of the polymer was determined to be 50.3% by chemical titration method, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.

[0063] Example 3

[0064] (1) L-lactide and maleic anhydride are added to a reaction kettle, and dicumyl peroxide as an initiator is added, and the reaction is carried out at a constant temperature under nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted L-lactide polymer; D-lactide and maleic anhydride are added to another reaction kettle, and dicumyl peroxide as an initiator is added, and the reaction is carried out at a constant temperature under nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted D-lactide polymer. The reaction temperature of the above two grafting modifications is 100°C, the reaction pressure is 40kPa, the reaction time is 3h, and the gas flow rate of the nitrogen flow protection is 3m / s; based on the weight of L-lactide or D-lactide, the amount of maleic anhydride added is 170% of L-lactide or D-lactide, and the amount of dicumyl peroxide is 1.0% of L-lactide or D-lactide.

[0065] (2) removing the L-lactide and D-lactide that did not participate in the grafting reaction in step (1) by vacuum distillation to obtain purified maleic anhydride grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature is 130° C.; the pressure is 20 kPa, and the time is 3 h.

[0066] (3) MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, respectively, while adding a nitrogen flow and negative pressure to obtain MA-LLA oligomers and MA-DLA oligomers; the reaction temperature of the low temperature prepolymerization is 135° C., the reaction time is 4.5 h, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3.5 m / s, and the catalyst stannous octoate is 3% of the weight of MA-LLA or MA-DLA; the initiator triphenylphosphine is 3% of the weight of MA-LLA / MA-DLA.

[0067] (4) The MA-LLA oligomer and the MA-DLA oligomer of step (3) are simultaneously added into a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and high-temperature reactive mixing and extrusion granulation are performed to finally obtain a maleic anhydride grafted poly-LD lactic acid copolymer material (MA-PLDLA); based on the weight of the MA-LLA oligomer, MA-DLA is 50% of the MA-LLA, and the antioxidant triphenyl phosphite is 4% of the MA-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 185°C.

[0068] Performance characterization: The right-angle tear strength of the maleic anhydride grafted poly LD lactic acid copolymer material was measured to be 152 KN / m, the elongation at break was 48%, the glass transition temperature was 99°C, and the molecular weight of the polymer was 3.25×10 5 The maleic anhydride grafting rate of the polymer was determined to be 53.4% ​​by chemical titration method, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.

[0069] Example 4

[0070] (1) L-lactide and maleic anhydride are added to a reaction kettle, and dicumyl peroxide is added as an initiator, and the reaction is carried out at a constant temperature under a nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted L-lactide polymer; D-lactide and maleic anhydride are added to another reaction kettle, and dicumyl peroxide is added as an initiator, and the reaction is carried out at a constant temperature under a nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted D-lactide polymer; the reaction temperature of the above two grafting modifications is 105° C., the reaction pressure is 45 kPa, the reaction time is 3.5 h, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of L-lactide or D-lactide, the maleic anhydride is 180% of the L-lactide or D-lactide, and the dicumyl peroxide is 1.5% of the L-lactide or D-lactide.

[0071] (2) removing the L-lactide and D-lactide that did not participate in the grafting reaction in step (1) by vacuum distillation to obtain purified maleic anhydride grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature is 130° C.; the pressure is 25 kPa, and the time is 3.5 h.

[0072] (3) MA-LLA and MA-DLA obtained in step (2) are prepolymerized at low temperature under the action of a catalyst and an initiator, respectively, while adding a nitrogen flow and negative pressure to obtain MA-LLA oligomers and MA-DLA oligomers; the reaction temperature of the low temperature prepolymerization is 140° C., the reaction time is 4.5 h, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3.5 m / s, and the catalyst stannous octoate is 4% of the weight of MA-LLA or MA-DLA; the initiator triphenylphosphine is 4% of the weight of MA-LLA or MA-DLA.

[0073] (4) The MA-LLA oligomer and the MA-DLA oligomer of step (3) are simultaneously added into a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and high-temperature reactive mixing and extrusion granulation are performed to finally obtain a maleic anhydride grafted poly-LD lactic acid copolymer material (MA-PLDLA); based on the weight of the MA-LLA oligomer, MA-DLA is 60% of the MA-LLA, and the antioxidant triphenyl phosphite is 5% of the MA-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 185°C.

[0074] Performance characterization: The right-angle tear strength of the maleic anhydride grafted poly LD lactic acid copolymer material was measured to be 160 KN / m, the elongation at break was 57%, the glass transition temperature was 104°C, and the molecular weight of the polymer was 3.48×105 The maleic anhydride grafting rate of the polymer was determined to be 58.6% by chemical titration method, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.

[0075] Example 5

[0076] (1) L-lactide and maleic anhydride are added to a reaction kettle, and dicumyl peroxide is added as an initiator, and the mixture is reacted at a constant temperature under a nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted L-lactide polymer; D-lactide and maleic anhydride are added to another reaction kettle, and dicumyl peroxide is added as an initiator, and the mixture is reacted at a constant temperature under a nitrogen flow and vacuum conditions to obtain a maleic anhydride grafted D-lactide polymer; the reaction temperature of the above two grafting modifications is 110° C., the reaction pressure is 55 kPa, the reaction time is 4 h, and the gas flow rate of the nitrogen flow protection is 4 m / s; based on the weight of L-lactide or D-lactide, the maleic anhydride is 200% of the L-lactide or D-lactide, and the dicumyl peroxide is 2.0% of the L-lactide or D-lactide.

[0077] (2) removing the L-lactide and D-lactide that did not participate in the grafting reaction in step (1) by vacuum distillation to obtain purified maleic anhydride grafted L-lactide (MA-LLA) and D-lactide (MA-DLA); the vacuum distillation temperature is 135° C.; the pressure is 30 kPa, and the time is 3.5 h.

[0078] (3) MA-LLA and MA-DLA obtained in step (2) are respectively subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, and nitrogen flow and negative pressure conditions to obtain MA-LLA oligomers and MA-DLA oligomers; the reaction temperature of the low-temperature prepolymerization is 140° C., the reaction time is 5 h, the reaction pressure is 400 kPa, the gas flow rate of the nitrogen flow protection is 4 m / s, and the catalyst stannous octoate is 6% of the weight of MA-LLA or MA-DLA; the initiator triphenylphosphine is 5% of the weight of MA-LLA or MA-DLA.

[0079] (4) The MA-LLA oligomer and the MA-DLA oligomer of step (3) are simultaneously added into a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and high-temperature reactive mixing and extrusion granulation are performed to finally obtain a maleic anhydride grafted poly-LD lactic acid copolymer material (MA-PLDLA); based on the weight of the MA-LLA oligomer, MA-DLA is 80% of the MA-LLA, and the antioxidant triphenyl phosphite is 6% of the MA-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 190°C.

[0080] Performance characterization: The right-angle tear strength of the maleic anhydride grafted poly LD lactic acid copolymer material was measured to be 148KN / m, the elongation at break was 44%, the glass transition temperature was 97°C, and the molecular weight of the polymer was 3.12×10 5 The maleic anhydride grafting rate of the polymer was determined to be 51.5% by chemical titration method, and the presence of terminal hydroxyl groups was determined by phthalic anhydride method.

[0081] Comparative Example 1

[0082] The polylactic acid graft copolymers are prepared by first polymerizing L-lactide or D-lactide and then grafting the obtained polylactic acid graft copolymers:

[0083] (1) L-lactide (LLA) is prepolymerized at low temperature under the action of a catalyst and an initiator, and under nitrogen flow and negative pressure to obtain LLA oligomers. The reaction temperature of the low temperature prepolymerization is 130°C, the reaction time is 3 hours, the reaction pressure is 300 kPa, the flow rate of the nitrogen flow is 3 m / s, and the amount of the catalyst stannous octoate added is 0.5 wt% of the amount of LLA used, based on the weight of L-lactide (LLA); the amount of the initiator triphenylphosphine added is 0.2 wt% of the amount of LLA used.

[0084] (2) The L-lactide (LLA) in step (1) is replaced by D-lactide (DLA), and the other steps are the same as step (1) to obtain DLA oligomer.

[0085] (3) adding the LLA oligomer obtained in step (1) and the DLA oligomer obtained in step (2) into a twin-screw extruder for polymerization reaction, adding maleic anhydride (MA) and an antioxidant, and subjecting the mixture to high-temperature reactive mixing, extrusion and granulation to obtain a maleic anhydride grafted polylactic acid material (MA-PLLA); the DLA oligomer is 30% of the LLA oligomer, the amount of maleic anhydride added is 15 wt% of the total weight of the LLA oligomer and the DLA oligomer (and the inventors have experimentally verified that even if the amount of maleic anhydride added continues to increase, the grafting rate does not increase), the amount of antioxidant triphenyl phosphite added is 2 wt% of the LLA oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing, extrusion and granulation is 180°C.

[0086] Product performance: The right-angle tear strength of the copolymer material was measured to be 102KN / m, the elongation at break was 12%, the glass transition temperature was 68°C, and the molecular weight of the polymer was 2.45×10 5 The maleic anhydride grafting rate of the polymer was determined to be 1.8% by chemical titration method; the presence of terminal hydroxyl groups could not be detected by chemical titration method.

Claims

1. A poly LD lactic acid graft copolymer, characterized in that: It is a compound having the general structure of formula I: Where R1, R2, ... and R n are independently selected from H or And R1, R2, ... and R n In the equation, R1, R2, ... and R n for The molar percentage is not less than 15%, preferably 15%-85%, more preferably 20%-80%, further preferably 30%-70%, most preferably 40%-60%.

2. The copolymer according to claim 1, characterized in that Its weight average molecular weight is 1.5×10 5 -4.5×10 5 .

3. The copolymer according to claim 1, characterized in that Its right-angle tearing strength is not less than 130kN / m, its elongation at break is not less than 35%, and its glass transition temperature is 90-110°C.

4. The method for preparing the poly LD lactic acid graft copolymer according to claim 1, comprising the following contents: (1) mixing L-lactide, maleic anhydride and an initiator to react to obtain maleic anhydride grafted L-lactide MA-LLA, and purifying the product; mixing D-lactide, maleic anhydride and an initiator to react to obtain maleic anhydride grafted D-lactide MA-DLA, and purifying the product; (2) mixing the MA-LLA, MA-DLA, catalyst and initiator obtained in (1), and prepolymerizing at low temperature to obtain MA-LDLA oligomer; (3) The MA-LDLA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain a maleic anhydride grafted poly-LD lactic acid copolymer material MA-PLDLA.

5. The preparation method according to claim 4, characterized in that: The initiator in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, and the amount of the initiator added is 0.1-5% by weight of the L-lactide or D-lactide.

6. The preparation method according to claim 4, characterized in that: The step (1) is carried out under a constant temperature reaction in an inert gas flow and vacuum conditions, the reaction temperature is 50-150° C., the reaction pressure is 2-100 kPa, and the reaction time is 0.5-10 h.

7. The preparation method according to claim 4, characterized in that: Based on the weight of L-lactide or D-lactide, the amount of maleic anhydride added is 100-300% of the L-lactide or D-lactide.

8. The preparation method according to claim 4, characterized in that: The purification in step (1) is to remove L-lactide and D-lactide that do not participate in the grafting reaction by vacuum distillation, and the vacuum distillation temperature is 100-200°C, the pressure is 0-100kpa, and the time is 1-10h.

9. The preparation method according to claim 4, characterized in that: In step (2), the catalyst is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride; and the initiator is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine.

10. The preparation method according to claim 4, characterized in that: In step (2), based on the weight of MA-LLA, the amount of the catalyst added is 0.2-10% of MA-LLA, and the amount of the initiator added is 0.1-10% of MA-LLA.

11. The preparation method according to claim 4, characterized in that: In step (2), the amount of MA-DLA added is 20-120% of the weight of MA-LLA.

12. The preparation method according to claim 4, characterized in that: Step (2) is low-temperature polymerization under inert gas flow and negative pressure conditions, the polymerization reaction temperature is 100-150° C., the reaction time is 2-15 hours, and the reaction pressure is 100-1000 kPa.

13. The preparation method according to claim 4, characterized in that: The antioxidant in step (3) is one of phosphites, alkyl polyphenols and thiobisphenols, and the amount of the antioxidant added is 1%-10% by weight of the MA-LLA oligomer.

14. The preparation method according to claim 4, characterized in that: The temperature of the polymerization reaction in step (3) is 150-250°C.

15. The preparation method according to claim 4, characterized in that: Step (3) uses a twin-screw extruder to realize the reaction process, adds MA-LLA oligomer, MA-DLA oligomer and antioxidant into the twin-screw extruder for polymerization reaction, and performs high-temperature reactive mixing and extrusion granulation to finally obtain maleic anhydride grafted poly LD lactic acid copolymer material.

16. Use of the poly LD lactic acid graft copolymer according to claim 1, wherein the copolymer is used in the fields of agricultural mulch films, food packaging and medical hygiene products.

Citation Information

Patent Citations

  • Preparation method for maleic anhydride-modified polylactic-co-glycolic acid

    CN103570884A

  • Polylactic acid compound preparation method

    CN104371082A

  • Technology for preparing high-molecular-weight MPLGA by directly grafting maleic anhydride onto PLGA

    CN105315412A

  • Method for modifying polylacticacid by adopting unsaturated cyclic anhydride or unsaturated cyclic imide, modified product and application

    CN1367189A

  • Method for modifying polylactic acid by adopting unsaturated cyclic acid anhydride or unsaturated cyclic acid imide and its application

    CN1495216A